MANIFESTASI MOTO “BERADAB, BERILMU, DAN BERDAKWAH” DALAM PENDIDIKAN KARAKTER SANTRI DI PONDOK PESANTREN YAA BUNAYYA - Muhamad Kenang Saputra Mulia; A. Arif Rofiki; A Ubaidillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the manifestation of the motto “Civilized, Knowledgeable, and Preaching” in the character education of students and to identify the factors influencing its manifestation at Yaa Bunayya Islamic Boarding School, Jayapura City. The study was motivated by the importance of character education in developing students who possess not only intellectual competence but also noble character and the ability to apply Islamic values in daily life. This research employed a descriptive qualitative method with a pedagogical approach. Data were collected through observation, in-depth interviews, and documentation involving the foundation chairman, boarding school leaders, teachers, students, and parents. The collected data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the manifestation of the motto has been implemented through the three dimensions of Thomas Lickona’s character education, namely moral knowing, moral feeling, and moral action. These values are internalized through learning activities, habituation, role modeling, supervision, and daily boarding school practices. Furthermore, the successful implementation of the motto is supported by three main factors: moral community, moral modelling, and moral discipline, which are reflected in a supportive social environment, consistent role models provided by educators, and effective disciplinary practices. Therefore, the motto “Civilized, Knowledgeable, and Preaching” functions not merely as an institutional slogan but as an educational philosophy that shapes students into individuals with good character, broad knowledge, and the ability to contribute positively to society through exemplary conduct and Islamic preaching.